2017
DOI: 10.1039/c7an01158j
|View full text |Cite
|
Sign up to set email alerts
|

Selective phosphatidylcholine double bond fragmentation and localisation using Paternò–Büchi reactions and ultraviolet photodissociation

Abstract: The effect of double bond functionalisation for selective double bond localisation by ultraviolet photodissociation of phosphatidylcholines is investigated. Paternò-Büchi reactions in nanoESI emitter tips enable attachment of acetophenone to double bonds of unsaturated phosphatidylcholines after 100 s of 254 nm light irradiation with about 50-80% reaction yield. Functionalized phosphatidylcholines dissociate upon 266 nm irradiation yielding double bond selective fragment ions in contrast to results for ultravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
0
35
0
2
Order By: Relevance
“…1f, for analysis of PC 16:0/18:1(9Z) standard, m/z 489 and m/z 578 were diagnostic ions for the C=C location while m/z 396 and m/z 466 could serve as diagnostic ions for C18:1 at sn-2 and C16:0 at sn-2. A systematic screening was performed for a group of carbonyl compounds 52,53 (Supplementary Fig. 7 and Supplementary Table 3) using the nanoESI-MS platform shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1f, for analysis of PC 16:0/18:1(9Z) standard, m/z 489 and m/z 578 were diagnostic ions for the C=C location while m/z 396 and m/z 466 could serve as diagnostic ions for C18:1 at sn-2 and C16:0 at sn-2. A systematic screening was performed for a group of carbonyl compounds 52,53 (Supplementary Fig. 7 and Supplementary Table 3) using the nanoESI-MS platform shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In combination with electrospray ionization (ESI‐)MS, several techniques have recently emerged that exploit chemical derivatization of C=C bonds and subsequent generation of diagnostic fragments in a CID experiment. These include ozone‐induced dissociation (OzID) of selected ions within a collision cell, epoxidation reaction with acetone enabled by a cold plasma, and on‐line Paternò–Büchi (PB) photo‐derivatization . Very recently, a combination of MALDI‐MSI and CID/OzID, performed in the linear ion trap of a modified MALDI‐LTQ Orbitrap Elite mass spectrometer, was used to visualize the distributions of db‐ and sn ‐positional isomers of several phosphatidylcholines (PC) in mouse brain .…”
Section: Figurementioning
confidence: 99%
“…Moreover, modifications of the initially introduced setup were reported, tackling particular drawbacks of this approach. For example, Wäldchen et al combined the PB reaction by ultraviolet photodissociation (UVPD), striving for an even higher selectivity in terms of the fragmentation via altered dissociation process [59]. Based on a different approach, Esch et al demonstrated the effect of charge switching, via derivatization with acetylpyridine, on the conversion to the targeted diagnostic fragments.…”
Section: Introductionmentioning
confidence: 99%